Teoría sociológica moderna - RITZER, George (Mc GRAW-HILL, 2002)
Otros descriptores: LUKACS, George; GRAMSCI, Antonio; HABERMAS, Jurgen; LUHMANN, Niklos; GOFFMAN, E.; HOMANS, G.; BLAN, Peter; ELIAS, Norbert; LEVI-STRAUSS, Claude; JAMESON, F.; BAUDRILLARD, Jean; BOURDIEU, Pierre; KHUN, Thomas; GLOBALIZACION